Maxillofacial Fractures: Midface and Internal Orbit—Part II: Principles and Surgical Treatment - Mast, Gerson; Ehrenfeld, Michael; Cornelius, Carl-Peter; Tasman, Abel-Jan; Litschel, Ralph (Facial Plastic Surgery, 2015)
Current clinical assessment and imaging techniques were described in part 1, and this article presents a systematic review of the surgical treatment principles in the management of midface and internal orbit fractures from initial care to definitive treatment, including illustrative case examples. New developments enabled limited surgical approaches by standardization of osteosynthesis principles regarding three-dimensional buttress reconstruction, by newly developed individualized implants such as titanium meshes and, especially for complex fracture patterns, by critical assessment of anatomical reconstruction through intraoperative endoscopy, as well as intra- and postoperative imaging. Resorbable soft tissue anchors can be used both for ligament and soft tissue resuspension to reduce ptosis effects in the cheeks and nasolabial area and to achieve facial aesthetics similar to those prior to the injury.
Keywords: midface fracture; Le Fort fracture; orbital fractures; zygomatic fracture; osteosynthesis face